E-cadherin adhesion molecule and syndecan-1 expression in various thyroid pathologies - Mitselou, A.; Ioachim, E.; Peschos, D.; Charalabopoulos, K.; Michael, M.; Agnantis, N.J.; Vougiouklakis, T. (Experimental Oncology, 2007)
Cadherins and syndecans are transmembrane glycoproteins implicated in cell-cell and cell-matrix adhesion. Impairment of cadherin and syndecan mediated adhesion is likely to constitute one of the main factors leading to the reduced cell-cell and cell-matrix adhesion characteristics of tumor cells and play a pivotal role in the acquisition of invasive and metastatic proprieties by neoplastic epithelial cells. Aim: To elucidate the role and alterations of syndecan-1 expression in comparison with those of E-cadherin in normal and pathological thyroid glands (TG). Methods: A total of 55 TG carcinomas, 40 TG adenomas, 40 cases of hyperplastic TG disorders and 20 cases of normal TG autopsy samples, were evaluated by immunohistochemistry. The staining intensity, and localization of syndecan-1 and E-cadherin in sequential sections were examined, and semi-quantified. Results: Immunostaining of syndecan-1 and E-cadherin was strong in normal follicular TG epithelial cells, and located mainly in basolateral membrane. No significant change was seen in either molecule in hyperplastic TG disorders compared with TG adenomas. A significant reduction in expression of both syndecan-1 and E-cadherin was seen in well-differentiated TG carcinomas as compared with normal TG epithelium (p = 0.0001 and p = 0.032, respectively). Similarly, there was a significant reduction of both molecules expression in poorly differentiated and anaplastic TG carcinomas compared to well differentiated tumors (syndecan-1: p = 0.0037; and E-cadherin: p = 0.075). Conclusion: Decreased E-cadherin and syndecan-1 expression along with decreasing cellular differentiation may be involved in the complex mechanism of progression of TG pathology. Кадгерины и синдеканы — это трансмембранные гликопротеины, участвующие в межклеточной адгезии и адгезии клеток
к матриксу. Изменения экспрессии этих молекул играют главную роль в приобретении инвазивного и метастатического
потенциала злокачественно трансформированными эпителиальными клетками. Цель: оценка роли экспрессии синдекана-1
и Е-кадгерина в ткани щитовидной железы в норме и при патологии. Методы: образцы ткани для иммуногистохимического
исследования взяли у 55 больных раком щитовидной железы (ЩЖ), 40 пациентов — с аденомой ЩЖ, 40 — с гиперпластическими
процессами ЩЖ, контролем служили 20 образцов неизмененной ткани ЩЖ (аутопсия). Результаты:
экспрессия синдекана-1 и Е-кадгерина в нормальных фолликулярных эпителиальных клетках ЩЖ выражена интенсивно,
с преимущественной локализацией в базолатеральной мембране. Не отмечали существенных различий в экспрессии
обеих молекул при гиперпластических процессах по сравнению с аденомами ЩЖ. Однако таковая значительно снижена
в образцах высокодифференцированной карциномы по сравнению с нормальным эпителием ЩЖ (p = 0,0001 и p = 0,032
соответственно), а также при низкодифференцированном и анапластическом раке по сравнению с высокодифференцированными
опухолями ЩЖ (p = 0,0037 для синдекана-1 и p = 0,075 для Е-кадгерина). Выводы: снижение экспрессии
синдекана-1 и Е-кадгерина, сопровождающееся снижением способности клеток к дифференциации, может быть частью
механизма прогрессирования заболеваний ЩЖ.